CRIMINAL SANCTIONS AND ACTIONS IN RELIGIOUS JUSTICE CRIME LAW ENFORCEMENT - Carto Nuryanto (UNISSULA, 2019)
Victims of drug abuse in the mandate of the Act should the victim run a rehabilitation, will remain in reality the victim immediately subjected to criminal penalties, so that there is a non-compliance with the law enforcement system carried out by the authorities with statutory regulations, weaknesses in the criminal sanction policy and actions in law enforcement in handling the current drug crime, as well as how the reconstruction of criminal sanctions policies and actions in the enforcement of the drug crime control system in realizing religious justice.